Meso-scale photospheric convection during chromospheric fan-shaped surge on light bridge - Yuzong Zhang; Jun Zhang; Wenda Cao; Shuhong Yang; Yunfei Yang; Jiangtao Su; Reizaburo Kitai; Xinjie Mao; Ding Yuan; Xin Huang; Xiaoshuai Zhu; Chunlan Jin; et al. (Discover Applied Sciences)
Abstract Recently, intermittent and aperiodic fan-shaped chromospheric surges have attracted significant attention, though their related photospheric dynamic signals remain unclear. This study examines seven such surges and their potential photospheric signals along a light bridge (LB) in NOAA AR 12371 over a period of 100 min using BBSO/GST observations. Each surge displays as dark, jet-like structures with nearly uniform amplitudes, aligned closely along the LB to form a long smooth upper edge. Simultaneously, the photospheric LB exhibits dynamic grains, including bright points and granules. Adjacent grains brighten, expand, and merge into a ‘grain group’ (GG), which span LB’s cross-section. As GG moves along the LB, its leading edge develops an arched structure. During GG formation, the local horizontal magnetic field direction undergoes significant deflection. Within the 100-min interval, 10 GGs were recorded, occurring intermittently and aperiodically. Notably, three photospheric GG-free intervals corresponded to three chromospheric surge-free intervals, with a temporal delay (80–712 s) between GG reappearance and surge recurrence. Our findings suggest that meso-scale photospheric GGs, larger than individual granules but smaller than the full extent of the LB, are closely related to chromospheric surges. A conceptual model integrating inverse turbulent cascades and flux tube interactions is proposed, unifying multi-scale energy transfer from photospheric convection to chromospheric reconnection.